Preparation and characterization of polyvinyl alcohol thin films: Rheological, physicochemical and functional properties - Morteza Abazari; Safa Momeni Badeleh; Soroush Barkhordari; Shahen Salih Mohammed; Mohammed Mahmood Ahmed; Muath Sheet Mohammed Ameen; Hossein Abdollahi (Heliyon, 2025)
In the present study, the basic and dynamic rheological properties of polyvinyl alcohol solutions were investigated in order to obtain desired solutions suitable for the thin film-forming process. To this end, polyvinyl alcohol solutions with different concentrations (2.5, 5, and 8 % w/v) were prepared, and their rheological behaviors were comprehensively investigated by different rheological techniques and models. According to the results, unusual rheological properties were obtained for different concentrations of polyvinyl alcohol in rheological measurements, such as strain amplitude, angular frequency, and temperature sweep tests, especially at higher concentrations. In this regard, a liquid-like behavior in the high strain, frequency, and temperature regions was observed for concentrated solutions, while a solid-like behavior was dominant in the low dynamic regions and concentrations. A higher elastic modulus plateau than loss modulus was obtained in the relatively low frequencies and temperatures as a gel with a network structure for lower concentrations of solutions, while higher concentrations exhibited similar results in opposite directions. Based on rheological results, the 5 % w/v solution was considered suitable for the thin film-forming process. The resultant thin films were analyzed using different physicochemical techniques to evaluate their various morphological, mechanical, thermal, and functional properties for application in different fields.